Genetic spectrum of renal disease for 1001 Chinese children based on a multicenter registration system. Issue 5 (25th July 2019) - Rao, Jia; Liu, Xiaorong; Mao, Jianhua; Tang, Xiaoshan; Shen, Qian; Li, Guomin; Sun, Li; Bi, Yunli; Wang, Xiang; Qian, Yanyan; Wu, Bingbing; Wang, Huijun; et al.
Abstract: To explore the approaches and diagnostic yield of genetic testing for renal disease in children, we describe the genotype and phenotype of the national cohort of children with renal disease from 13 different regions of China recruited from 2014 to 2018 by building up the multicenter registration system (Chinese Children Genetic Kidney Disease Database, CCGKDD). Genetic diagnosis was confirmed in 42.1% of our cohort of 1001 pediatric patients with clinical suspicion of a genetic renal disease. Of the 106 distinct monogenetic disorders detected, 15 accounted for 60.7% of genetic diagnoses. The diagnostic yield was 29.1% in steroid resistant nephritic syndrome (SRNS), 61.4% in cystic renal disease, 17.0% in congenital anomalies of the kidney and urinary tract (CAKUT), 62.3% in renal tubular disease/renal calcinosis, and 23.9% for chronic kidney disease (CKD) 3 to 5 stage with unknown origin. Genetic approaches of target gene sequence (TGS), singleton whole‐exome sequencing (WES) and trio‐WES were performed with diagnostic rates of 44.8%, 36.2%, and 42.6%, respectively. The early use of trio‐WES could improve the diagnostic rate especially in renal tubular disease and calcinosis. We report the genetic spectrum of Chinese children with renal disease. Establishment of the CCGKDD will improve the genetic work on renal disease. Abstract :